A NEW MODEL FOR SINGLE FACILITY LOCATION BASED ON SERVICE LEVEL - Javid, A Ahmadi; Davoudpour, H (The South African Journal of Industrial Engineering, 2009)
This paper studies a new continuous single facility location problem. In this problem the